Design and Implementation of Robotank for Room Monitoring and Exploration - M. Nur Imam DJ; Dadan Nur Ramadhan; Sugondo Hadiyoso (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
A robot is a mechanical device that can perform physical tasks, either autonomously or with human control. Robots began to be used for monitoring in areas that have narrow spaces and/or dangerous areas. So that this robot must be able to carry out monitoring with a remote control system. Therefore, in this study, a robotank is designed that can perform space exploration with remote control. Robotank is designed to use a track and wheel that can pass through various terrains and it has dimensions of 11.8 x 10.8 x 9.1 cm. Robotank is equipped with a camera to monitor in real-time. Robotank can move from one point to another by controlling using a remote control system with a maximum distance of 20 meters in line of sight terrain and 16 meters in non-line of site fields, with an average speed of 0.84 m/s. Robotank can work for 1 hour 52 minutes. With this robotank, it is hoped that it can be used for exploration of areas or rooms that have small spaces and dangerous.